Investigating the Iron Plating and Stripping of Anolytes for All-Iron Redox-Flow Batteries - Marius Engler; Michael Stich; Christoph Baumer; Andreas Bund (J)
All-iron redox-flow batteries (AIRFB) are capable of addressing the needs for cost-effective long-term storage of renewable energies. Currently, a major limitation of AIRFB performance is the half-cell reaction of the anolyte utilising the redox couple Fe/Fe2+. In this work, the performance of sulphate and chloride-based iron electrolytes was investigated by combining cyclic voltammetry (CV) and electrochemical quartz crystal microbalance (EQCM). The investigations demonstrate that complexing agents exert a detrimental influence on the kinetics of plating/stripping reactions, resulting in diffusivity reduction, while favouring hydrogen evolution reaction (HER). The coulombic (plating) efficiency was found to be 87.1% at −1.2 V vs. Ag/AgCl (sat’d) at pH 3.5, while the coulombic efficiency in oxidation sweep (stripping) was observed to be 100% in an electrolyte containing 0.8 M FeCl2 and 3 M NH4Cl. In the context of iron deposition, the most crucial factors are the suppression of HER, and the influence of diffusion limitations, as well as the role of additives in this process to achieve a high reversibility. It is evident that the investigated complexing agents of glycine, malic acid and malonic acid are inadequate for battery-compatible, efficient properties, given that the overvoltages for the charge transfer reaction are too high and parasitic HER reduces coulombic efficiencies. Ultimately, the choice of deposition parameters from EQCM and electrolyte composition reduced to 0.8 M FeCl2, and 3 M NH4Cl can optimise the battery efficiencies as such.